FIRE FIGHTING ROBOTIC VEHICLES - Prof. Shaikh Z. A. R.; Mr. Pintu Kumar Mahato; Mr. Chitranjan Kumar; Mr. Aniruddh Ghayale; Mr. Mujjfar Shaikh (International Journal of Innovations in Engineering Research and Technology, 2024)
The project is designed to develop a fire fighting robot using Arduino uno . The robotic vehicle is loaded with water pump which is controlled by servos. An ATMega 328 microcontroller is used for the desired operation. At the transmitting end using commands are sent to the receiver to control the movement of the robot either to move forward, and left or right etc. At the receiving end tow motors are interfaced to the microcontroller where two of them are used for the movement of the vehicle and the one to position the robot. The ultrasonic sensor adequate range with obstacle detection, while the receiver driver module used to drive DC motors via motor driver IC for necessary work. A water tank along with water pump is mounted on the robot body and its operation is carried out from the microcontroller output through appropriate command from the transmitting end. The whole operation is controlled by an ATmega 328 microcontroller. A motor driver IC is interfaced to the microcontroller through which the controller drives the motors,three ir flame sensors are fixed on robot chassis to sense the fire and to reach the destination to putoff the fire.